IIEECP Intervention in Teaching-Learning Process: An Experience - Kurundawade, Sandeep R.; Kavale, Sanjeev M. (Journal of Engineering Education Transformations, 2018)
Many innovative pedagogical practices are having significant influence on effective teaching learning of various courses across the globe. Basic Sciences have an important role to play in building base for core engineering subjects even though they are courses of short duration in most of the Indian engineering institutions.But, it has been observed that students tend to take these courses lightly. The same has been observed by several teachers across the globe. Rizaet al, of Universiti Kebangsa an Malaysia,in their work, mentioned that students see this basic knowledge as difficult and not quite useful. Therefore, it is essential to make some efforts in experimenting with such courses in their design and pedagogical practices. Indo-Universal Collaboration for Engineering Education(IUCEE) and IGIP designed International Engineering Educator Certification Program (IIEECP) provided a platform where many pedagogical practices were introduced to the participants that helped to incorporate them in course delivery and hence make the delivery of content more effective. The main objective of this work is to study the intervention of various pedagogical practices in effective learning and also performance of students. This paper speaks about the implementations of learned pedagogical practices from IIEECP like active learning, collaborative learning and teaching with technology and their impact in Engineering Chemistry course for freshman students. Results of the study gave a clear impression of improvement in student engagement and learning. In semester and end semester assessment results also support the improved learning.